Kapita Selekta Media, Budaya dan Masyarakat di Era Digital: Algoritma Penyaring Berita pada Narasi Pertikaian Israel-Palestina di Media Sosial - Sarina, Angelita; Pontoh, Frily Cristy; ., Ronal; Humaira, Talitha Oktavia; Dwihadiah, Desideria Lumongga (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This article aims to assess the use of news filtering algorithms in presenting narratives of the Israel-Palestine conflict on social media. Employing a communication science approach, the research will delve into how these algorithms influence news consumption patterns, shape opinions, and impact user satisfaction with the information they receive. By gaining a comprehensive understanding of these dynamics, the article seeks to provide valuable insights into the role of technology in shaping publicperspectives on sensitive geopolitical conflicts.